Development of Rooftop Photovoltaic Resources in Factory Building Complexes and Energy Efficiency Improvement Under Self-Generation and Self-Consumption Mode - Zhiliang, Wang (Asian Journal of Social and Humanities, 2025)
In response to national energy conservation and emission reduction requirements, the company has systematically implemented rooftop photovoltaic (PV) development across its three thermal power plants to promote green, low-carbon transformation. This qualitative case study analyzes operational data, project documentation, and performance indicators from these sites over two years. By utilizing rooftops of dormitories, offices, and factory buildings, a distributed PV system for self-consumption was constructed, reducing overall plant power consumption and boosting energy efficiency. Quantitative results show annual external electricity purchases dropped by 8–12%, with peak daytime self-consumption rates of 85–90%. The system yielded replicable outcomes in management, operations, and collaboration. Through comprehensive planning, standardized construction, robust maintenance, and performance evaluation, PV operational stability and profitability improved significantly, offering thermal power firms a path to "promote construction through utilization and emission reduction through construction." Beyond cost savings, distributed PV forms a cornerstone for sustainability strategies, enabling hybrid systems that balance fossil-based generation with renewables. This study provides a replicable framework for industrial-scale rooftop PV and empirical evidence for self-consumption models in thermal power settings.